Efeitos dento-esqueléticos maxilares do aparelho extrabucal de tração oblíqua alta e de tração oblíqua baixa em crianças e adolescentes com maloclusão de classe II - Cunha, Anna Laura Serpa da (2022)
Introduction: Class II malocclusion is defined by a maxillomandibular discrepancy in the anteroposterior direction. The extraoral appliance (AEB) is a good alternative as a first stage of orthodontic treatment in children and adolescents with this type of malocclusion. To opt for a certain extraoral traction, resulting from high oblique force or low oblique, the patient's facial growth pattern should be considered. Objectives: To analyze on profile teleradiographs the effects of the exclusive use of high oblique traction AEB (AEBa) and low oblique traction AEB (AEBb) on the first permanent upper molars, permanent upper central incisors and maxillary bone structures in children and adolescents with Class II malocclusion. Materials and Methods: 59 patients, with a mean age of 9.9 ± 1.24 years, were evaluated to compare the differences between the onset (T0) and immediately after the end of treatment (T1) with AEBa and AEBb through angular measurements on profile teleradiographies. Twenty-one patients were treated with AEBa and thirty-eight patients were treated with AEBb. The measurements were compared between the evaluation times (T0 vs. T1), within each group, with the paired Student's t-test. The initial values and the difference between the evaluation times (T1-T0) were compared between the groups (AEBa vs. AEBb) with the Student's t-test for independent samples. Results: Both the AEBa and the AEBb caused inclination of the first permanent upper molars to the distal, represented by the statistically significant decrease in the values of 6.PP and 6.SN between the evaluation times (P < 0.001), but the distal inclination significantly more accentuated was in the AEBb group (6.PP = -13.05 ± 10.94o; 6.SN = -13.95 ± 10.98o) than in the AEBa group (6.PP = -3.6 ± 5.18o; 6.SN = -4 ± 4.7o) (P < 0.001). In the AEBb group, there was projection of permanent upper central incisors, detected by the increase of 1.PP (1.85 ± 3.48o; P < 0.001), in addition to clockwise rotation of the palatal plane, identified by the statistically significant increase of the PP measurement. SN (1 ± 1.99o; P < 0.001). Conclusions: The AEBa and the AEBb caused distal inclination of the first permanent upper molars, being more accentuated with the use of AEBb. The AEBb caused a slight projection of permanent upper central incisors and a small displacement of the jaw clockwise. There was no difference between AEBa and AEBb regarding maxillary skeletal effects.